Impacts of land use, population, and climate change on global food security - Molotoks, Amy; Smith, Pete; Dawson, Terence P. (Food and energy security, 2021)
In recent years, global hunger has begun to rise, returning to levels from a decade ago. Climate change is a key driver behind these recent rises and is one of the leading causes of severe food crises. When coupled with population growth and land use change, future climate variability is predicted to have profound impacts on global food security. We examine future global impacts of climate variability, population, and land use change on food security to 2050, using the modeling framework FEEDME (Food Estimation and Export for Diet and Malnutrition Evaluation). The model uses national food balance sheets (FBS) to determine mean per capita calories, hence incorporating an assumption that minimum dietary energy requirements (MDER) remain constant. To account for climate variability, we use two Representative Concentration Pathway (RCP) scenarios from the Intergovernmental Panel on Climate Change (IPCC), alongside three Shared Socio‐economic Pathway (SSP) scenarios incorporating land use and population change within the model. Our results indicate that SSP scenarios have a larger impact on future food insecurity, in particular because of projected changes in population. Countries with a projected decrease in population growth had higher food security, while those with a projected rapid population growth tended to experience the worst impacts on food security. Although climate change scenarios had an effect on future crop yields, population growth appeared to be the dominant driver of change in undernourishment prevalence. Therefore, strategies to mitigate the consequences of projected population growth, including improved maternal health care, increasing equality of access to food at the national level, closing the yield gap, and changes in trade patterns, are essential to ensuring severe future food insecurity is avoided. The global Food Estimation and Export for Diet and Malnutrition Evaluation model uses FAO methodology to estimate national undernourishment prevalence as a proportion of population undernourished. Using a baseline period of 2000‐2002, projections for 2050 even under the lowest global impact scenario show significant prevalence of undernourishment. This emphasises the need for quick action, particularly in low‐income countries to avoid future food insecurity.